2007
DOI: 10.1128/aem.00507-07
|View full text |Cite
|
Sign up to set email alerts
|

At Least Two Origins of Fungicide Resistance in Grapevine Downy Mildew Populations

Abstract: Quinone outside inhibiting (QoI) fungicides represent one of the most widely used groups of fungicides used to control agriculturally important fungal pathogens. They inhibit the cytochrome bc 1 complex of mitochondrial respiration. Soon after their introduction onto the market in 1996, QoI fungicide-resistant isolates were detected in field plant pathogen populations of a large range of species. However, there is still little understanding of the processes driving the development of QoI fungicide resistance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
148
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(156 citation statements)
references
References 54 publications
6
148
0
2
Order By: Relevance
“…An example of contrasted mating systems in two closely related species is given by Plasmopara viticola and P. halstedii, oomycetes responsible respectively for the downy mildews of grapevine and sunflower. Molecular markers showed that the two species displayed similar levels of genetic diversity (Chen et al, 2007;Delmotte et al, 2006). The homothallic species P. halstedii showed considerable heterozygote deficit (F IS = 0.95), probably due to limited dispersal ability before mating and thus lack of available sexual partners in the field (Giresse et al, 2007), while the populations of P. viticola only slightly deviated from HardyWeinberg proportions (Chen et al, 2007;Delmotte et al, 2006).…”
Section: Mating Systemsmentioning
confidence: 96%
See 1 more Smart Citation
“…An example of contrasted mating systems in two closely related species is given by Plasmopara viticola and P. halstedii, oomycetes responsible respectively for the downy mildews of grapevine and sunflower. Molecular markers showed that the two species displayed similar levels of genetic diversity (Chen et al, 2007;Delmotte et al, 2006). The homothallic species P. halstedii showed considerable heterozygote deficit (F IS = 0.95), probably due to limited dispersal ability before mating and thus lack of available sexual partners in the field (Giresse et al, 2007), while the populations of P. viticola only slightly deviated from HardyWeinberg proportions (Chen et al, 2007;Delmotte et al, 2006).…”
Section: Mating Systemsmentioning
confidence: 96%
“…Molecular markers showed that the two species displayed similar levels of genetic diversity (Chen et al, 2007;Delmotte et al, 2006). The homothallic species P. halstedii showed considerable heterozygote deficit (F IS = 0.95), probably due to limited dispersal ability before mating and thus lack of available sexual partners in the field (Giresse et al, 2007), while the populations of P. viticola only slightly deviated from HardyWeinberg proportions (Chen et al, 2007;Delmotte et al, 2006). Fungi exhibit a variety of other ways to recombine genetic information than sexuality, gathered under the terms of parasexuality or somatic recombination (Bos, 1996).…”
Section: Mating Systemsmentioning
confidence: 99%
“…However, the fungicides of this family have been widely used to control downy mildew due to P. viticola and powdery mildew due to E. necator on grapevine, through one to three treatments per year, since their introduction in 2001 in France. As a consequence, the G143A mutation is now widespread in most French populations of P. viticola, within two different cytb haplotypes (15), resulting in poor disease control when strobilurins are used alone. In contrast, resistance associated with the same cytb alteration took longer to be selected in E. necator and was first recorded in France in 2008 (19), highlighting the …”
Section: Discussionmentioning
confidence: 99%
“…In some cases the strength of selection can lead to rapid fixation of resistance alleles in fungal populations after only a single year of fungicide use (reviewed in Grimmer et al, 2014). In this regard, fungicide resistance evolution is a phenomenon similar to antibiotic resistance evolution (Davies & Davies, 2010), but the literature describing the evolutionary processes that generate, spread and maintain novel resistance alleles in fungal plant pathogens is relatively limited (Chen et al, 2007;Brunner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%